Phytochemicals, Bioactivity, and Utilization of Etlingera elatior as a Medicinal Plant - Muhammad Ainur Rosyid Ridho; Ratri Dwi Indriani; Arfiana Tanti Wulansari; Kristanti Indah Purwani (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Etlingera elatior, commonly known as torch ginger, is a plant widely used as a cooking spice. Native to Southeast Asia, E. elatior is not only valued for its culinary uses but also for its high nutritional content. It is also used medicinally, including as a treatment for typhoid fever and various other diseases. The bioactivity of this plant has been extensively studied. It has antioxidant, antibacterial, antifungal, tyrosinase-inhibiting, cytotoxic, and hepatoprotective properties. E. elatior acts as an antimicrobial, antioxidant, anticancer, anti-hyperglycemic, anti-hyperuricemia, anti-inflammatory, larvicidal, skin-whitening, anti-aging, and wound-healing agent. These biological activities are attributed to its rich content of phytochemical compounds, including phenols, flavonoids, glycosides, saponins, tannins, steroids, and terpenoids. Given its wide range of biological activities and chemical compounds, E. elatior warrants further research to contribute to the development of natural medicinal plants in Indonesia.